Effects of the annular eclipse on the surface O3 in yunnan province, China - Tian, Yufeng; Li, Jingyuan; Yang, Chaolei; Cui, Jingqi; Shen, Fuzhen; Lu, Jianyong; Xiong, Shiping; Wei, Guanchun; Li, Zheng; Zhang, Hua; Yang, Guanglin; Wu, Yewen; et al. (Frontiers in Environmental Science, 2022)
The impact of the annual solar eclipse, starting on 21st June 2020, attributable to surface ozone concentration (O3) has been investigated in this study. To estimate the influence of the solar eclipse on O3 better, the variations of one reaction precursor of ozone production [nitrogen dioxide (NO2)], coupled with the meteorological factors (including Total Solar Irradiance (TSI), Temperature (T), and Relative Humidity (RH)), were analyzed in Yunnan Province, China. The results show observed O3 decreases from the beginning of the eclipse, reaching its minimum value when the eclipse left Yunnan province. During the period of the solar eclipse, the O3 decrease lasted for 20 h with a reduction of more than 40%. The reduction of TSI lasted for 5 h with a maximum at -90%. Simultaneously, the temperature decreased but the relative humidity increased during the reduction in solar radiation. O3 exhibits a significantly positive correlation with temperature and a negative correlation with relative humidity. However, NO2 did not show a clear response with changes lasting for 4 h. O3 and NO2 show a negative correlation. The influence of CO on O3 is minor except for Kunming. Thus, O3 in seriously polluted cities is more sensitive to NO2 and CO during the eclipse, such as in Kunming.